Postcosecha y comercialización deL cacao CCN-51 en la agrícola Onesgar S.A. del Cantón Buena Fe. - Cedeño Álava, Viviana Marcela (2016)
The research project entitled "POSTHARVEST and marketing of the cocoa CCN-51 in the AGRICOLA ONESGAR S.A. of EL CANTON good faith", aimed at evaluating the processes of post-harvest and commercialization of cacao CCN-51, in the Agricola Onesgar S.A. in the Canton good faith, in the 2012-2014 period. It is located in the canton San Jacinto in good faith, av. 7 of August/Northern Variant. The methods used in the research were applied, descriptive and investigative. 54 surveys were conducted for data collection. Cocoa producers have an approximate time of 10 years as clients of the company, the type of cocoa that mostly produce is the CCN-51, the frequency with which harvested product is less than 15 days, months in which obtained higher yields are: February, March, October and November; the subsequent work of harvest that are dry in motor and ferment in bags for three days. Not sold on baba, the little percentage that sells your product in this way, has done it by necessity and seem like their prices decrease time in the fermentation process; cocoa storage usually not done since his sale is immediate. The marketing of the alkalised COB is little known by farmers, for it are unaware of its advantages and disadvantages. The prices and attention have loyal customers, indicating that prices received were $100 to 120 per quintal of cocoa, making them a discount from 11 to 20% moisture. The total costs of marketed in the year 2012 with $286.423,10; for the 2013 was $563.503,94; and in 2014, the total was $3 ' 459.392, 78; and the total of marketing for 2012 with $6.001,49; $21.345,23 of liquid utility 2013 and 2014 said $ - 91.629, 22. Palabras key: postharvest, marketing, cocoa CCN-51, and costs administrative